Renaissance eLearning: - Chapnick, Samantha (Pfeiffer, 2005)
The same people who brought you the most widely used guide to preparing for eLearning are bringing passion back to your learning and training programs. The authors culled through over 400 eLearning programs, hundreds of popular entertainment pieces, and interviews with over 100 people in widely disparate areas to answer a simple question: What will make eLearning have as much impact as popular culture? Renaissance eLearning is the answer. It has everything you need to infuse eLearning with the same magnetism and addictive powers of the typical video game, song, movie, or other form of entertainment